Dielectric properties of chitosan and two ionic derivatives: Effect of counter anions. (1st December 2022) - Salama, Ahmed; Mohamed, Fathia; Hesemann, Peter
Abstract: We report herein the dielectric properties response of two ionic chitosan derivatives. More specifically, we report here chitosan derivatives bearing guanidinium groups, prepared through the reaction between chitosan and cyanamide when scandium (III) triflate is present. The anionic counter ions of the guanidinium groups could be changed by working either in acetic acid or hydrochloric acid. In this way, two chitosan derivatives, namely N-guanidinium chitosan acetate (GChAc) and N-guanidinium chitosan chloride (GChCl), were produced. The materials were investigated by 13 C solid state NMR, FT-IR spectroscopy, SEM and TEM analysis and compared with the parent chitosan. Dielectric spectroscopy has been used to study the relaxation behavior of the parent chitosan and the new chitosan derivatives over wide ranges of temperature and frequency, indicating that local motion is affected by counter ions. Due to these features, these materials are interesting candidates as high-power electrical materials for green technological applications. Graphical abstract: Unlabelled Image